2021
DOI: 10.3389/fclim.2021.713708
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface Hydrophobicity on the Structure and Dynamics of CO2 and CH4 Confined in Silica Nanopores

Abstract: Advancing a portfolio of technologies that range from the storage of excess renewable natural gas for distributed use to the capture and storage of CO2 in geological formation are essential for meeting our energy needs while responding to challenges associated with climate change. Delineating the surface interactions and the organization of these gases in nanoporous environments is one of the less explored approaches to ground advances in novel materials for gas storage or predict the fate of stored gases in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…A remarkable decrease in CH 4 uptake was observed for IRH- 7 (0.08 mol kg −1 ) over IRH- 6 (1.03 mol kg −1 ) under 100 kPa at 298 K. This can be justified by the narrowing of the pore aperture of IRH- 7 , which significantly reduces the adsorption of CH 4 of kinetic diameter greater than the pore diameter of this porous material. 37 IRHs 6 and 7 maintain the same exponential CO 2 adsorption behavior after several adsorption cycles without any loss of capacity (Fig. S20 and S21†).…”
Section: Resultsmentioning
confidence: 72%
“…A remarkable decrease in CH 4 uptake was observed for IRH- 7 (0.08 mol kg −1 ) over IRH- 6 (1.03 mol kg −1 ) under 100 kPa at 298 K. This can be justified by the narrowing of the pore aperture of IRH- 7 , which significantly reduces the adsorption of CH 4 of kinetic diameter greater than the pore diameter of this porous material. 37 IRHs 6 and 7 maintain the same exponential CO 2 adsorption behavior after several adsorption cycles without any loss of capacity (Fig. S20 and S21†).…”
Section: Resultsmentioning
confidence: 72%
“…Notably, the thickness of the first adsorption layer is consistently greater by approximately 10% than that of the second adsorption layer. This difference originates from the surface roughness on the pore walls (Supporting Information, Figure S1) and, as such, may be influenced by the surface functionalization in various porous media …”
Section: Resultsmentioning
confidence: 99%
“… 7 Furthermore, lowering the silanol concentration on the silica surface reduced the amount of CO 2 adsorbed. 6 Another molecular dynamics simulation by Mohammed et al 8 showed that CO 2 and CH 4 both preferred the silanol sites over CH 3 -terminated silica surfaces. These computational studies support increasing the silanol concentration to increase the affinity of natural gas components to silica surfaces.…”
Section: Introductionmentioning
confidence: 99%